Semi-supervised learning models for document classification: A systematic review and meta-analysis - Alex Cevallos-Culqui; Claudia Pons; Gustavo Rodriguez (Inteligencia Artificial, 2023)
The continuous increase of digital documents on the web creates the need to search for information patterns that allow the categorization of organizational documents to generate knowledge in an institution. An Artificial Intelligence technique for this purpose is text classification, it for its application uses labels (previously categorized documents) with supervised (with labels) or unsupervised (without labels) training models. Both traditional models with their advantages and disadvantages have been joined into semi-supervised models that extract the best qualities of each one, however, the labeling process involves resources and time that try to be optimized to improve classification accuracy.